Pituitary volumes in hypochondriac patients - Atmaca, Murad; Yildirim, Hanefi; Sec, Semih; Kayali, Alperen (Pergamon-Elsevier Science Ltd, 2010)
To date, no study has examined the pituitary volumes in patients with hypochondriasis. In the present study, we evaluated pituitary volumes in patients with hypochondriasis and healthy controls. Twenty individuals with hypochondriasis (ten males, ten females), aged 20 to 48 years, and healthy controls were included into the study. The pituitary volumes were obtained. Volumetric measurements were made with T1-weighted coronal MRI images, with 2.4-mm-thick slices, at 1.5 T, and Were done blindly. Volumetric measurements did not demonstrate group differences in the brain measurements, i.e., whole brain volume, white, and gray matter volumes (P>0.05). We found significantly smaller pituitary volumes of the whole group of hypochondriac patients compared to healthy controls (age and ICV as covariates). To conclude, the results from the current investigation suggest that hypochondriac patients had smaller pituitary volumes compared with healthy controls. This could be the keystone to a better understanding of the neurobiological basis of hypochondriasis. (C) 2009 Published by Elsevier Inc.
Keywords: Hypochondriasis; MRI; Pituitary; Volumetric